Pengaruh Risiko Audit, Sistem Pengendalian Mutu, Dan Supervisi Terhadap Penghentian Prematur Atas Prosedur Audit - Saputra, Risman Ristiana; Sarwoko, Haris (Jambura Economic Education Journal, 2025)
Measurement of the impact of audit risk, quality control system, and supervision on early audit procedure termination is the goal of this study. With a one-month data collecting period, the assessment type employs an objective quantitative methodology. Seventy-five respondents who satisfied the purposive sampling criteria were included in the evaluation sample, which included 10 public accounting firms in the South Jakarta region. SmartPLS version 4.0 was the statistical tool used for the data analysis procedure in this investigation. There are differences, according to the study's findings, where audit risk and supervision have a positive impact on early audit procedure termination while the quality control system has a negative impact. At the same time, the three variables have positive effects on early audit procedure termination.  Additionally, it would be preferable to broaden the study's variables for readers and authors in the future.  It will be feasible to have enough and competent information about the elements that might impact the early termination of audit operations by including additional variables.